2001
DOI: 10.1159/000049695
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ATP-Sensitive Potassium Channel Plays a Dominant Role in Ischemic Preconditioning of Rabbit Heart

Abstract: Background: The ATP-sensitive potassium (KATP) channel has been shown to be important in the ischemic preconditioning (IPC) response. Recently, the mitochondrial rather than the sarcolemmal KATP channel has been focused on due to its energy-modulating property. Hence, this study was undertaken to elucidate the role of the mitochondrial KATP channel in IPC by modulating the mitochondrial KATP channel in isolated perfused rabbit hearts. Methods: Seven hearts served as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
(34 reference statements)
0
18
0
Order By: Relevance
“…Nonselective K ATP openers such as bimakalim also opened mitochondrial channels (Garlid et al, 1996), although this occurred within the dose range where sarcolemmal activation was observed. Mitochondrial K ATP have been shown to be important in mediating pharmacological cardioprotection and preconditioning (Liu et al, 1998;Nakai et al, 2001) BMS-191095 was shown to be highly selective for mitochondrial K ATP and has no effects on smooth muscle or pancreatic cells (Grover et al, 2001). Although this compound is of great interest, only in vitro and ex vivo (Langendorff hearts) studies have been reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonselective K ATP openers such as bimakalim also opened mitochondrial channels (Garlid et al, 1996), although this occurred within the dose range where sarcolemmal activation was observed. Mitochondrial K ATP have been shown to be important in mediating pharmacological cardioprotection and preconditioning (Liu et al, 1998;Nakai et al, 2001) BMS-191095 was shown to be highly selective for mitochondrial K ATP and has no effects on smooth muscle or pancreatic cells (Grover et al, 2001). Although this compound is of great interest, only in vitro and ex vivo (Langendorff hearts) studies have been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous K ATP subtypes exist and seem to be differentially expressed in various tissues (Inoue et al, 1991;Atwal et al, 1993;Grover et al, 1995a;Chutkow et al, 1996;Inagaki et al, 1996). Pharmacological data suggest that mitochondrial K ATP activation is critical for cardioprotection and that this channel is distinct from sarcolemmal channels (Garlid et al, 1996(Garlid et al, , 1997Liu et al, 1998;Nakai et al, 2001). Clear pharmacological separation between smooth muscle relaxation and cardioprotection has been reported for several K ATP openers such as BMS-180448 and BMS-191095 (Atwal et al, 1993;Grover et al, 1995bGrover et al, , 2001Rovnyak et al, 1997) (chemical structures shown in Fig.…”
mentioning
confidence: 99%
“…Recent studies indicate a protective effect of mitochondrial ATP-sensitive K ? channel rather than sarcolemmal sarcK ATP channel opening on myocardial ischemiareperfusion injury [2][3][4][5]. The K ATP channel from cardiac myocyte mitochondria has been reported to be 2000 times more sensitive to diazoxide than the cardiomyocyte sarcolemmal K ATP channels, indicative of the fact that two distinct receptor subtypes coexist within the cardiomyocyte.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is thought that K ATP channels exert a protective property in myocardial ischemic diseases (Fujita and Kurachi, 2000). Recent studies hint that mitochondrial K ATP channel opening rather than sarcolemmal (surface) K ATP channel opening may play a dominant role in affording cardioprotection in ischemic hearts due to its energy-modulating property (Liu et al, 1998;Garlid et al, 1997Garlid et al, , 1996Nakai et al, 2001). The K ATP channel from cardiac myocyte mitochondria has been reported to be 2000 times more sensitive to diazoxide than the cardiomyocyte sarcolemmal K ATP channels, indicative of the fact that two distinct receptor subtypes coexist within the cardiomyocyte (Liu et al, 1998;Garlid et al, 1997Garlid et al, , 1996.…”
Section: Introductionmentioning
confidence: 99%